Fraud Hexagon and Intellectual Intelligence on Academic Fraud: The Moderating Role of Student Behavior - Vanessa Berliana Santoso; Anna Sumaryati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the factors leading to academic fraud among accounting students, focusing on the predictive power of the Fraud Hexagon Theory and intellectual intelligence. It also investigates the role of student ethical behavior as a moderating variable. Using a quantitative approach, data was collected from 111 respondents selected through purposive sampling. The data was subsequently analyzed using SPSS version 25. The findings revealed that the Fraud Hexagon model was only partially validated. Three of its six dimensions emerged as significant predictors of academic fraud: rationalization, capability, and opportunity. Conversely, pressure, ego, and collusion showed no significant influence. The study also found no statistical relationship between a student's intellectual intelligence and their tendency to commit fraud. Furthermore, student ethical behavior did not effectively moderate the influence of the significant Fraud Hexagon factors. The study concludes that academic fraud is a complex phenomenon primarily triggered by internal justification, individual capabilities, and external opportunities. The lack of correlation with intellectual intelligence suggests that cognitive ability is not an inherent barrier to dishonest acts. These findings underscore that a strong ethical character is the most powerful safeguard against fraud, highlighting the irreplaceable role of ethics education in fostering academic integrity.